Characteristics of the boards of directors at firms listed on Nasdaq Baltic - Donatas Voveris; Julija Savicke; Greta Drūteikienė (Problems and Perspectives in Management, 2023)
The board of directors plays a pivotal role in firm governance, endorsing strategic choices, coordinating operations, ensuring regulatory compliance, and furnishing organizational support. This paper aims to examine the characteristics of the boards of directors and the guidelines for board composition in publicly listed firms in the Baltic countries. The analysis consists of two stages. The first is a quantitative investigation of the attributes of boards (board size, CEO duality, gender diversity, foreign directors, board committees, board independence, and directors’ occupational background) targeting 35 firms and 187 directors. The second is a qualitative analysis of guidelines for board composition of Nasdaq Baltic-listed firms in Estonia, Latvia, and Lithuania. The results reveal that the attributes of boards of directors do not raise concerns. Despite their relatively smaller scale in contrast to the United States or Europe, the boards of Nasdaq Baltic companies align effectively with their respective firm sizes. Notably, CEO duality is absent in Estonian and Latvian listed firms, while it is only partially evident in Lithuania. Moreover, directors’ heterogeneous professional backgrounds distinctly contribute to these boards’ overall enhancement. While the existence of board committees is strongly recommended, they are primarily implemented as a tool for controlling.